Menopausal hormone therapy affects quality of life in multimorbid late postmenopausal women - N. V. Izmozherova (Акушерство, гинекология и репродукция, 2021)
Aim: to evaluate an impact of menopausal hormone therapy (MHT) on late postmenopausal multimorbid women’s quality of life (QoL).Materials and Methods. 132 late postmenopausal women were enrolled to the study and were divided into two groups: group 1 consisted of 66 subjects with moderate multimorbidity and Charlson Comorbidity Index (CCI) < 3; group 2 (66 patients) had high multimorbidity (CCI ≥ 3). Women receiving or not MHT were subdivided in both groups. SF-36 questionnaire was used to assess QoL, Hospital Anxiety and Depression scale (HADS) – for evaluating emotional status, MMSE test (Mini-Mental State Examination) – for cognition evaluation. Modified Menopausal Index (MMI) was calculated as well.Results. Women with a low level of comorbidity who had previously received MHT have a significantly higher QoL. The median age for subjects was 69 [65; 71] years, median CCI score was 3.5 [2.5; 5.0]. In addition, in group 2 there were found significantly lower physical functioning (p < 0.001), role-physical functioning (p = 0.028), physical health (p = 0.002) domains, as well as more severe persistent menopausal symptoms (p = 0.011) and depression (p = 0.043). History of MHT in group 1 was associated with higher levels of physical functioning (p = 0.033) and role-physical functioning (p = 0.023), whereas in group 2 MHT was associated with better cognition (p = 0.028) and lower depression symptoms compared with those lacking history of MHT.Conclusion. Multimorbidity in late postmenopausal women was associated with impaired QoL physical domains. MHT allows to effectively improve QoL in women with moderate multimorbidity and to protect cognitive state to higher level as well as reduce depression symptoms in women with severe multimorbidity.